# Solve equation |f^-1(x)|= 1+f^-1(x)

## Homework Statement

f(x) = (2x-3)/(x-1)
Solve the equation |f^-1(x)|= 1+f^-1(x)

## Homework Equations

I'm pretty sure f^1(x) = (-3+x)/(x-2)

## The Attempt at a Solution

I am not sure what solve means. Do i need to plug in values?

Mentor

## Homework Statement

f(x) = (2x-3)/(x-1)
Solve the equation |f^-1(x)|= 1+f^-1(x)

## Homework Equations

I'm pretty sure f^1(x) = (-3+x)/(x-2)

## The Attempt at a Solution

I am not sure what solve means. Do i need to plug in values?
No, that wouldn't be very productive unless you just happened to pick a value that works.

I believe the problem is asking you to find the value of x that makes the equation a true statement.
Also, yes, the inverse is ##f^{-1}(x) = \frac {x - 3} {x - 2}##
Replace ##f^{-1}(x)## by this expression in the equation you're given and get x all by itself.

• whitsona
Homework Helper
Dearly Missed

## Homework Statement

f(x) = (2x-3)/(x-1)
Solve the equation |f^-1(x)|= 1+f^-1(x)

## Homework Equations

I'm pretty sure f^1(x) = (-3+x)/(x-2)

## The Attempt at a Solution

I am not sure what solve means. Do i need to plug in values?

Make life easier for yourself by letting ##f^{-1}(x) = y##, so your equation is ##|y| = 1 + y##. First figure out the value of ##y##, then figure out what must be ##x## to give you ##f^{-1}(x) = y##.

• whitsona